DANCING THROUGH THE (NEXT) MINEFIELD, 1 OR HOW AND WHY SHOULD WE READ THE STORIES OF GERMAN WOMEN PRISONERS?. (October 2014) - Colvin, Sarah; Woodford, Charlotte; Colvin, Sarah
ABSTRACT This article considers the circumstances of production and reception of texts by women prisoners in Germany since 1949, and what makes such writing 'worth reading'. I suggest that (a) some of the issues faced by a researcher of prisoner writing now – particularly those around the visibility of the writing and its perceived aesthetic status – reprise issues faced by feminist literary critics in years gone by, and (b) that recognition might assist in the development of appropriate methodologies for approaching prisoner texts by men and women writers.